Etiology and nature of intervertebral disc degeneration and its correlation with low back pain - Koji Koyama; Koichi Nakazato; Kenji Hiranuma (Journal of Physical Fitness and Sports Medicine, 2015)
Low back pain (LBP) is a common musculoskeletal disorder that affects the general and athletic populations. Intervertebral disc degeneration (IDD) is one of the causes of LBP and a current topic in the orthopedic and sports medicine fields. The correlation between IDD and LBP seems controversial. In Part I of this review article, we examine the etiology and nature of intervertebral disc degeneration in terms of classification and definitions of lumbar IDD, prevalence of lumbar IDD, and possible risk factors for lumbar IDD. In Part II, we compare IDD and LBP in general and athletic populations.